2003
DOI: 10.1097/01.ccm.0000054867.01688.d1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Emergency Department Sepsis (MEDS) score: A prospectively derived and validated clinical prediction rule*

Abstract: In patients with suspected infection, this model identifies significant correlates of death and allows stratification of patients according to mortality risk. As new therapies become available for patients with sepsis syndromes, the ability to predict mortality risk may be helpful in triage and treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
385
11
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 456 publications
(423 citation statements)
references
References 30 publications
17
385
11
10
Order By: Relevance
“…Our results are similar to the AUC of 0.78 found among "allcomers" with sepsis in the original MEDS score validation study. 10 Again, patient selection may have accounted for these differing findings, because although our study represented a sicker group of patients, only around half the patients in our study were admitted to the ICU. Our study included patients in whom critical care admission was not deemed either necessary or appropriate or who died in the ED prior to transfer to the ICU.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Our results are similar to the AUC of 0.78 found among "allcomers" with sepsis in the original MEDS score validation study. 10 Again, patient selection may have accounted for these differing findings, because although our study represented a sicker group of patients, only around half the patients in our study were admitted to the ICU. Our study included patients in whom critical care admission was not deemed either necessary or appropriate or who died in the ED prior to transfer to the ICU.…”
Section: Discussionmentioning
confidence: 51%
“…22 For example, the MEDS score, the most frequently studied model, used the clinical decision to draw a blood culture as the enrollment criteria in its derivation cohort. 10 While subsequently found to be predictive of mortality up to 1 year among ED patients with sepsis, 11 other authors found that among patients with septic shock undergoing early goal-directed therapy (EGDT) resuscitation, predictive performance of MEDS for outcome was poor. 14 An additional limitation of the MEDS score is that a large weighting is given to a subjective assessment of short-term mortality by the treating clinician.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary analyses of the primary outcome included odds ratio with adjustment for Mortality in Emergency Department Sepsis (MEDS) score components, sensitivity analyses for missing data, learning-curve analysis, and adherence-adjusted analysis. We conducted prespecified subgroup analyses by testing interactions between the effect of EGDT and the degree of protocolized care (in the usual-care group), age, MEDS score, 23 SOFA score, and the time from presentation at the emergency department to randomization.…”
Section: Discussionmentioning
confidence: 99%